Biodegradable silica nanocapsules enable efficient nuclear-targeted delivery of native proteins for cancer therapy. (March 2023) - Du, Wei; Du, Shubo; Dong, Xiao; Bai, Hua; Jiang, Jiamin; Hao, Shiping; Yang, Fen; Xiao, Qicai; Zhang, Bei; Ge, Jingyan; Gao, Liqian; Li, Lin; et al.
Abstract: Cell nucleus is the desired subcellular organelle of many therapeutic drugs. Although numerous nanomaterial-based methods have been developed which could facilitate nuclear-targeted delivery of small-molecule drugs, few are known to be capable of delivering exogenous native proteins. Herein, we report a convenient and highly robust approach for effective nuclear-targeted delivery of native proteins/antibodies by using biodegradable silica nanocapsules (BSNPs ) that were surface-modified with different nuclear localization signals (NLS) peptides. We found that, upon gaining entry to mammalian cells via endocytosis, such nanocapsules (protein@BSNP -NLS) could effectively escape from endolysosomal vesicles with the assistance of an endosomolytic peptide (i.e., L17E), accumulate in cell nuclei and release the encapsulated protein cargo with biological activities. Cloaked with HeLa cell membrane, DNase@BSNP -NLS/L17E-M (with L17E encapsulated) homologously delivered functional proteins to cancer cell nuclei in tumor-xenografted mice. In vitro and in vivo anti-tumor properties, such as long blood circulation time and effective tumor growth inhibition, indicate that the nuclear-targeted cell-membrane-cloaked BSNPs (DNase@BSNP -NLS/L17E-M) platform is a promising therapeutic approach to nuclear related diseases.